2019
DOI: 10.1186/s40780-019-0137-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of neonatal hypoglycemia after ritodrine therapy in premature labor: a retrospective cohort study

Abstract: Background Ritodrine hydrochloride (RD), a β2-adrenergic agonist, is widely used as a tocolytic medication to suppress premature labor, but can cause neonatal hypoglycemia, a potentially severe side effect. We examined the incidence and risk factors of neonatal hypoglycemia following maternal intravenous administration of RD. Methods This was a retrospective study of neonates, who had birth weight of ≥2000 g and were delivered at 36 weeks gestation or later in Kanazawa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Doctor et al (29) found that SGA infants are 5 times more likely to develop hypoglycemia compared to AGA infants. The link between low birth weight and infant hypoglycemia has been confirmed in other studies as well (30)(31)(32). This is most likely due to decreased energy deposits and perinatal compromise.…”
Section: Discussionsupporting
confidence: 60%
“…Doctor et al (29) found that SGA infants are 5 times more likely to develop hypoglycemia compared to AGA infants. The link between low birth weight and infant hypoglycemia has been confirmed in other studies as well (30)(31)(32). This is most likely due to decreased energy deposits and perinatal compromise.…”
Section: Discussionsupporting
confidence: 60%
“…Belonging to the class of drugs known as β2-adrenergic receptor agonists, ritodrine’s primary mechanism of action is to stimulate β2-receptors on smooth muscles in the uterus, leading to relaxation and reduced contractions. However, its use has been linked to an increased risk of neonatal hypoglycemia due to its ability to inhibit insulin secretion from pancreatic beta cells, which may result in decreased glucose uptake by tissues ( 32 , 33 ). Therefore, when considering the use of ritodrine during labor and delivery, it is critical to weigh its potential risks against benefits and make informed clinical decisions.…”
Section: Discussionmentioning
confidence: 99%
“…71 The time interval to predict the incidence of neonatal hypoglycemia was approximately 6 hours after delivery (sensitivity 82.8%, specificity 63.9%). 68 Sustained hypoglycemia has not been observed in babies delivered 5 or more days after the end of tocolytic therapy. 71 In one case, hypoglycemia was severe and recurrent.…”
Section: Selective and Nonselective β-Blockers (β-Adrenergic Receptor...mentioning
confidence: 99%
“…67 The prevalence of hypoglycemia was 41.4 to 61.7% in newborns exposed to ritodrine alone, 42.9% in the ones exposed to both MgSo4 and ritodrine, and 8.2 to 22.2% in nonexposed controls. 67,68 No patient had hypoglycemia in a case series of neonates exposed to salbutamol or terbutaline. 69 Risk factors and potential confounders: a multivariable logistic regression analysis using the "Hypoglycemia set" listed among the independent risk factors for hypoglycemia cesarean section, SGA infants, and delivery to a mother treated with ritodrine alone or in combination with MgSO4.…”
Section: Selective and Nonselective β-Blockers (β-Adrenergic Receptor...mentioning
confidence: 99%